Synthesis of the fluorohydridoborate anions [BHF3]− and [1-HF2B-9, 12-X2-closo-1, 2-C2B10H9]− (X = H, I): deboronation of 1, 2- and 1, 7-dicarba-closo-dodecaboranes with anhydrous [Me4N]F. Issue 90 (21st October 2016) - Duda, Katharina; Himmelspach, Alexander; Landmann, Johannes; Kraus, Florian; Finze, Maik
Abstract : The [BHF3 ] − anion represents the first example of an anion of the series [BH n F4− n ] − ( n = 1–3), which is obtained via deboronation of closo -1, 2-C2 B10 H12 or closo -1, 7-C2 B10 H12 with anhydrous [Me4 N]F. Abstract : Deboronation of closo -1, 7-C2 B10 H12 and 1-R 1 - closo -1, 2-C2 B10 H12 (R 1 = Me, Ph) with anhydrous [Me4 N]F yields [Me4 N][BHF3 ] that is the first structurally characterized anion of the series [BH x F4− x ] − ( x = 1–3). Deboronation of 9, 12-R 2 2 - closo -1, 7-C2 B10 H12 (R 2 = H, I) gives a mixture of [Me4 N][BHF3 ] and [Me4 N][1-HF2 B-9, 12-R 2 2 - closo -1, 2-C2 B10 H9 ].